Soil Application Multi Micro Nutrient Fertilizer Mixtures (MMM) Influenced in Groundnut Yield - P. V. Mahatale; M. Y. Ladole; E. R. Vaidaya; N. K. Patke; G. S. Gaikwad (International Journal of Economic Plants)
A field experiment was conducted with a RBD with three replicates having Sixteen treatments of Soil application of 20, 40 and 60 kg ha-1 of Zinc High, Easy Mix, Vasundhara, Multinelf 16 and Boracal 12 multi-micronutrient mixtures (MMM) for Groundnut to ascertain the best matching  mixture for maximum yield enhancement during summer 2011–12, 2012–13 and 2013−14 at Oilseeds Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola, Maharashtra, India. The Recommended Dose of fertilizer i.e. 25:50:0 NPK kg ha-1 was used. Nitrogen @ 25 kg ha-1 and Phosphorus @ 50 kg ha-1 were applied as basal dose and doses of multi-micronutrient fertilizer was given at sowing. Pooled results revealed that treatment (T15) i.e. Mixture of Zinc, Ferrous iron, Boron, calcium and magnesium (Multinelf 16)  @ 60 kg ha-1 recorded significantly higher pod yield (3284 kg ha-1) over remaining treatments excluding Easy mix (3145 kg ha-1), Zinc High (3059 kg ha-1), Vasundhara (3018 kg ha-1) and Boracal (2803 kg ha-1) @ 60 kg ha-1 over its higher and lower level at the time of basal application. However, 100-kernal weight influenced significantly due to application of different Multi-micronutrient fertilizers mixture. Similarly, fetched significantly higher net return (` 96492 ha-1) and B:C ratio 3.18  followed by Easy mix @ 60 kg ha-1 (` 1 92377 ha-1, 3.12), Zinc High @ 60 kg ha-1 (` 88259 ha-1, 3.00) Vasundhara @ 60 kg ha-1 (` 85233 ha-1, 2.95) and  Boracal 12 @ 60 kg ha-1 (` 77883 ha-1, 2.81)  over left other  treatments.